Pastoral do surdo no Brasil: uma modalidade de inclusão social da diversidade auditiva - Silva, Érica Nelcina da (2022)
SILVA, Érica Nelcina da. Pastoral of the Deaf in Brazil: a modality of social inclusion of hearing diversity. Doctorate in Sciences of Religion at the Pontifical Catholic University of Goiás (PUC/GOIAS), 2022. Line of Research: Religion and Social Movements. The inclusion of the deaf in the daily actions of religious life is one of the great challenges for religious communities in Brazil. The objective of this work is to analyze the process of inclusion (or exclusion) of the deaf in the Catholic Church, based on the work of the Pastorals for the Deaf in Brazil. We want to identify the political-religious proposals of inclusion adopted by Catholic religious leaders and investigate the effective participation of the deaf in the Churches, as well as the strategies adopted by the Catholic movements to promote the connection of the deaf with the sacred. We question whether participation in pastoral activities for the deaf helps the deaf to feel more socially included, in order to reinforce their dignity. The methodology used was an online survey, with semi-structured interviews with a time frame in the year 2022, together with bibliographic research in published studies on the subject. We followed four stages in this investigation, deepening the concepts in each one and applying them to empirical research: religion, exclusion, inclusion and Pastoral of the Deaf. The concepts were discussed based on the contributions of Émile Durkheim, Max Weber, Otto Marques da Silva, Romeu Kazumi, Maria Teresa Eglér Mantoan, César Augusto de Assis Silva, Luiz Carlos Dutra, Karin Lillian, Strobel, Fraternity Campaign 2006, Serge Paugam, Simon Schwartzman, inclusive legislation among other theorists who are a reference in this topic. To better understand the reality experienced by the deaf, an empirical study was carried out through the application of a questionnaire containing twelve open and closed questions. The questionnaire was submitted to three different groups of people involved in the problem: agents of the Pastoral of the deaf, the deaf who attend the Pastoral of the in Brazil and Catholic religious leaders responsible for activities to include the deaf. The field research was carried out in a non-face-to-face manner, online via WhatsApp, in the 19 regional offices of the Pastoral of the deaf of the Catholic Church in Brazil. 162 interviews were carried out with representatives of the three mentioned groups. In addition, a survey was carried out with questions in Libras recorded on video and sent to the participants. The data collected and analyzed allowed us to affirm that, for the deaf, the Pastoral of the deaf constitutes a modality of inclusion in the religious community and, through it, in the rest of Brazilian society.